An Investigation of Insulin Resistance and Cachexia Relation in Patients with Metastatic Gastrointestinal Malignancies - Ebrahim Farashi; Ahmad Mahmoodpour; Aliakbar Movassaghpour Akbari; Zohreh Sanaat; Parvin Sarbakhsh; Seyed Hadi Chavoshi; Mortaza Raeisi; Parya Valizadeh; Saba Ghaffary (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: Insulin resistance has been suggested as one of the known metabolic disorders during cachexia. This study hypothesized that cachexia in cancer patients might be related to insulin resistance as early as cachexia development. Methods: This study was performed on 46 patients with metastatic gastrointestinal cancer. Anthropometric characteristics and biochemical markers were assessed at baseline, second and third month. Insulin resistance was assessed using the homeostasis model assessment-estimated insulin resistance (HOMA IR) method. SFQ-36 questions were used to assess the patients' quality of life at baseline, second and third months. Results: Anthropometric characteristic was significantly associated between pre-cachectic and non-pre-cachectic patients in third month. Cholesterol (P-value = 0.93), albumin (P-value: 0.82), and serum creatinine (P-value = 0.88) in pre-cachectic patients decreased over three months. There was an increasing trend of insulin resistance between pre-cachectic and non-pre-cachectic patients in third month. Cholesterol had an upward trend with a significant relation in cachectic patients [(P-value = 0.00), (P-value = 0.03), (P-value = 0.01)]. We detected a decreasing trend of insulin resistance between cachectic and non-cachectic patients from second to third month (P-value = 0.04). SFQ evaluation had no significant relation with cachectic status. Conclusion: Previous studies showed that the use of NSAIDs, progesterone's, corticosteroids, COX-2 inhibitors, anabolic agents and drugs targeting inflammatory cytokines may be beneficial for improving of symptoms of cachexia. Significant relation between anthropometric variables with pre-cachexia and cachectic conditions was concluded. Patients' outcome and its relation with insulin resistance demonstrated a significant relation between the cachectic and non-cachectic patients in the third month. We also detected the increased serum cholesterol level in cachectic patients, moreover, higher cholesterol levels in expired cachectic patients than in the living.